2020
DOI: 10.1111/acel.13107
|View full text |Cite
|
Sign up to set email alerts
|

Muscle atrophy‐related myotube‐derived exosomal microRNA in neuronal dysfunction: Targeting both coding and long noncoding RNAs

Abstract: In mammals, microRNAs can be actively secreted from cells to blood. miR‐29b‐3p has been shown to play a pivotal role in muscle atrophy, but its role in intercellular communication is largely unknown. Here, we showed that miR‐29b‐3p was upregulated in normal and premature aging mouse muscle and plasma. miR‐29b‐3p was also upregulated in the blood of aging individuals, and circulating levels of miR‐29b‐3p were negatively correlated with relative appendicular skeletal muscle. Consistently, miR‐29b‐3p was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…MiR-34a is highly express in aged mouse skeletal muscle and oxidative stress treated C2C12 cells, then these EVs home to bone marrow leading to BMSCs senescence via repressing SIRT1 expression (Yang et al, 2020). Role of EV-miR-1, miR-133a, miR-27, miR-29b-3p, and miR-34a in osteosarcopenia wait to explore.…”
Section: Age-related Bone-muscle Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-34a is highly express in aged mouse skeletal muscle and oxidative stress treated C2C12 cells, then these EVs home to bone marrow leading to BMSCs senescence via repressing SIRT1 expression (Yang et al, 2020). Role of EV-miR-1, miR-133a, miR-27, miR-29b-3p, and miR-34a in osteosarcopenia wait to explore.…”
Section: Age-related Bone-muscle Crosstalkmentioning
confidence: 99%
“…Elevated miR-34a in the aging muscle can account for muscle metabolic dysfunction, while decreased SIRT1 activity in aging muscles is associated with impaired muscle performance ( Mohamed et al, 2014 ; Kukreti and Amuthavalli, 2020 ). Yang et al (2020) reported that miR-29b-3p is increased in the plasma of aging mice and humans, differentiated atrophic C2C12 myotube could release miR-29b-3p-loaded EVs to induce neuronal dysfunction. miR-29b was shown to contribute to several types of muscle atrophy ( Li et al, 2017 ).…”
Section: Skeletal Muscle-derived Ev-micrornasmentioning
confidence: 99%
“…25 Evidence is accruing showing that interventions that combine lifestyle modification, physical exercise, cognitive training, and disease management have multiple physiocognitive benefits; [7][8][9]26,27 however physio-cognitive outcomes have been little studied. 25 In a study from 2020, we found that miR-29b-3p, which promotes neuronal cell death, is secreted from atrophying skeletal muscle, 28 which implies synchronous effects of physio-cognitive decline in the ageing process. In the PreDIVA trial, a 6-year vascular risk factor control intervention did not reduce incident dementia or disability.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, lncRNAs show more cell type-specific expression patterns than protein-coding genes, which supports the hypothesis that lncRNA is of functional importance. LncRNAs can be used as the organizational framework of subcellular structure to regulate protein localization or activity, and some lncRNAs can regulate global or local gene expression in trans or cis by influencing RNA polymerase II recruitment or inducing chromatin remodeling [ 36 ].…”
Section: The Emerging Roles Of Competing Endogenous Rna (Cerna) In Hccmentioning
confidence: 99%